2020
DOI: 10.1016/j.neo.2020.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Niche-derived soluble DLK1 promotes glioma growth

Abstract: Highlights Astrocytes secrete DLK1 after exposure to hypoxia or irradiation. Soluble DLK1 promotes stemness in glioma, in part by increasing HIF-2alpha stabilization. High levels of soluble DLK1 are associated with tumor aggressiveness and lethality.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
(55 reference statements)
0
12
0
Order By: Relevance
“…Interestingly, there are reports of extracellular matrix-anchored VEGF, along with other growth factors [ 68 , 69 ]. We previously identified soluble Delta Like Non-Canonical Notch Ligand 1 (DLK1) as a factor that promotes glioma growth and stemness and is secreted in the medium of hypoxic astrocytes [ 19 ]. Together, these findings suggest that hypoxic astrocytes could be involved in maintaining the stem-like cell phenotype of glioma cells by secreting soluble factors or remodeling the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, there are reports of extracellular matrix-anchored VEGF, along with other growth factors [ 68 , 69 ]. We previously identified soluble Delta Like Non-Canonical Notch Ligand 1 (DLK1) as a factor that promotes glioma growth and stemness and is secreted in the medium of hypoxic astrocytes [ 19 ]. Together, these findings suggest that hypoxic astrocytes could be involved in maintaining the stem-like cell phenotype of glioma cells by secreting soluble factors or remodeling the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia has been associated with an increase in glioma stem-like cell properties [ 4 , 10 , 11 ], glioma growth [ 12 ], and treatment resistance [ 13 , 14 ], as well as changes in cancer cell metabolism and pH [ 15 , 16 ]. Our lab and others have shown that differential stabilization of HIF factors in glioma stem-like cells maintains the stemness phenotype of these cells [ 5 , 17 , 18 , 19 , 20 , 21 ]. Hypoxic niches contain not only tumor cells, but also other cell types in the tumor microenvironment [ 5 , 22 ] that are also affected by low oxygen tension.…”
Section: Introductionmentioning
confidence: 99%
“…phenotype, and self-renewal abilities, mainly through the stabilization of HIF-2alpha levels 11 (Fig. 3).…”
Section: Dlk1 In Cancer and Cancer Stem Cell Nichesmentioning
confidence: 99%
“…8,50,[86][87][88][89][90][91] In particular, DLK1 overexpression has been associated with increased aggressiveness and poor outcome in glioblastoma (GBM), hepatocellular carcinoma, ovarian, prostate, and lung cancer. 11,47,49,50,90,92,93 Indeed, more and more evidence suggests that therapy resistance and relapse are mostly due to the survival of cancer cells presenting with the stemness phenotype, typically enriched in specialized microenvironmental niches, and that DLK1 can play a role in the regulation and maintenance of this phenotype.…”
Section: Dlk1 In Cancer and Cancer Stem Cell Nichesmentioning
confidence: 99%
See 1 more Smart Citation